Winter annual grass weed management in winter wheat - Pester, Todd A., author; Westra, Philip, advisor; Nissen, Scott, advisor; Quick, James, committee member; Ward, Sarah, committee member (Colorado State University. Libraries, 2001)
The objective of this dissertation was to enhance integrated weed management strategies for controlling winter annual grass weeds in winter wheat. The research consisted of a three-pronged approach evaluating cultural practices, herbicide-resistant crop technology, and weed genetic diversity. Field studies were conducted to evaluate the effects of combining multiple cultural practices on controlling jointed goatgrass in a winter wheat-fallow cropping system. Jointed goatgrass growth and population were effectively reduced in treatments that included a tall wheat cultivar with a more open-crown growth habit, increased wheat planting density, and reduced-tillage. Delayed planting usually reduced wheat yield without reducing jointed goatgrass production and sub-surface nitrogen applications did not significantly increase wheat competitive advantage. Wheat cultivars with resistance to imazamox herbicide are being developed that will facilitate selective control of jointed goatgrass, downy brome, and feral rye. These three weed species respond differently to imazamox postemergence treatments with feral rye demonstrating more tolerance than jointed goatgrass or downy brome. A series of laboratory studies identified that imazamox absorption was >90% in all three species and the differential control of jointed goatgrass and feral rye was attributed to differences in herbicide translocation and metabolism. Weed genetic diversity influences genetic response to selection pressure and may influence the success of chemical and cultural weed management practices. For example, the level of genetic diversity within jointed goatgrass may influence introgression of herbicide-resistant genes from wheat to jointed goatgrass through herbicide-resistant allele frequencies. RAPD and AFLP fingerprinting techniques generated over 650 molecular markers among eight U.S. and 50 Eurasian jointed goatgrass accessions of which 5% were polymorphic. Cluster analyses showed relatively small genetic distances among jointed goatgrass accessions. The lack of genetic diversity within jointed goatgrass suggests the evolution of the species was relatively recent and the subsequent polyploidy provided sufficient plasticity for adaptation to a wide geographic range without significant mutation and selection. The results of this research have increased our knowledge of winter annual grass weed biology and ecology and should contribute to the development of successful integrated management systems for these weeds in winter wheat.
Keywords: agronomy